Relevance of Ancient Sundanese Manuscript "Bujangga Manik" to Aspects of Sustainable Development Goals (Sdg’s) Through Literary Anthropology Study - Isnendes, Chye Retty; Haerudin, Dingding; Hendrayana, Dian; Kusumawardhana, Gelar Taufiq; Harya, Karguna Purnama (Journal of Ecohumanism, 2024)
The research was motivated by two things, namely the scientific concept of literary anthropology which is interdisciplinary with one of the characteristics of focusing on ethnography and the significance of the ancient Sundanese literary manuscript Bujangga Manik in the Sundanese literary and cultural treasures as a presentation of human thought in its day and an inexhaustible source of inspiration. The problem that arises is whether the manuscript can become a hypogram for the awakening of new thoughts and developments in addressing issues of environmental problems, especially climate change that is rapidly leading to global warming. Therefore, the world community is simultaneously calling for a green campaign, also known as the issue of Sustainable Development Goals or SDG’s. To answer this, the descriptive analytical method will be used with the steps of collecting data and analyzing it in two stages. The problems to be answered are: 1) the main character’s activities, reasons, and consequences, and 2) the relevance of the research results to the SDG’s program. The character’s activities are very important because they are related to signs that represent humans in their time. The relevance of SDG’s will show that this manuscript is able to be empowered and cross the current time span.